Implementasi Kebijakan Penyelenggaraan Perlindungan Anak Di Kabupaten Rokan Hulu - Melani Sahputri; Hasim As'ari (UIR Press, 2021)
This research was conducted with the aim of being able to find out and explain how the implementation of child protection policies and the inhibiting factors in implementing child protection in Rokan Hulu Regency. The implementation theory used is the Merille S. Grindle theory which contains two variables, namely the content of policy and the policy environment (implementation context). The type of research used is descriptive qualitative research. Data collection techniques using interviews, observation and documentation.The results in the study show that the implementation of child protection has not been implemented properly, including the degree of change desired, policy programs, resources, power, interests, and strategies of policy actors, institutional characteristics, level of compliance and response from implementation. So that there are still obstacles that occur, namely: (1) insufficient budget in providing treatment for child victims of violence. (2) lack of human resource capacity, inadequate facilities in implementing policies. (3) differences in public perception. (4) the organization has not yet formed the UPTD for the protection of women and children which spe.cifically handles child violence, causing an overload of tasks within the organization’s scope.